Melacak prinsip pemikiran Pendidikan Islam melalui Filsafat Klasik; Socrates, Plato dan Aristoteles. - Trya Imamatul Istiqomah; Aulia Salsabila; M. Yunus Abu Bakar (JOURNAL SAINS STUDENT RESEARCH, 2024)
How the emergence of ancient philosophy can influence Islamic education. This article explores the emergence of ancient philosophy and its influence in the perspective of the philosophy of Islamic education. Starting from the thoughts of Greek philosophers such as Socrates, Plato, and Aristotle, the concept of education they developed became an important foundation for the development of education in the Islamic world. Socrates with his dialogical method, Plato with the concept of education in the “Republic", and Aristotle with his empirical approach, all contributed to character building, the development of reason, and the attainment of wisdom. As Islamic civilization absorbed and adapted Greek philosophy, Muslim scholars integrated these ideas into the framework of Islamic teachings, resulting in a unique blend of Greek rationality and Islamic spirituality. This article explores how Islamic philosophy of education took shape through interaction with ancient philosophy, as well as how this intellectual legacy continues to influence the overarching concept of education in the Islamic tradition, which emphasizes the formation of the whole person, the harmonization of reason and faith, and the achievement of balance in the lives of individuals and society.